Thymine glycol lesions terminate chain elongation by DNA polymerase I in vitro. - Clark, J M (1986)
Single-strand circular DNA from bacteriophage M13mp9 was chemically modified with osmium tetroxide to introduce specifically cis-thymine glycol lesions, a major type of DNA damage produced by ionizing radiation. An oligonucleotide primer was extended on damaged and undamaged templates using either the large fragment of E. coli pol I or T4 DNA polymerase. The reaction products were analysed by electrophoresis alongside a DNA sequence ladder. Synthesis on the damaged templates terminated at positions opposite thymine bases in the template. These results indicate that cis-thymine glycol lesions in single-strand DNA constitute blocks to synthesis by DNA polymerases in vitro. Surprisingly, replication halts after the correct nucleotide, dAMP, is inserted opposite the lesion. These results imply that the primary effect of the thymine glycol lesion is suppression of DNA synthesis and that the lesion is not a potent mutagen.